Sentiment Analysis of Unilever Stock Performance During the Palestine-Israel Boycott Crisis: A Study on the Stockbit Platform - Firdausa, Annisya Zahro; Indraswari, Citra Rahayu (Contemporary Studies in Economic, Finance and Banking, 2026)
This study aims to examine investor sentiment regarding Unilever stock performance following the implementation of the Boycott, Divestment, and Sanction (BDS). Amid the intense air and ground assaults by the Israel Defense Forces (IDF) since October 7, 2023, resulting in thousands of casualties, global outrage has sparked calls for boycotts against companies associated with or supporting Israel. This research identifies a gap in understanding how such geopolitical shape investor sentiment. Analysis of Stockbit discussions highlights a shift in investor perspectives, with geopolitical concerns influencing their decisions on Unilever’s stock.